PENGEMBANGAN NASTAR DENGAN SUBTITUSI TEPUNG PISANG KEPOK UNTUK HIDANGAN HARI RAYA - Kusuma, Alan; Ratnaningsih, Nani (Prosiding Pendidikan Teknik Boga Busana, 2023)
The center of the largest banana producer in Indonesia is in the province of Lampung. The Central Statistics Agency (BPS) reported that bananas are the largest horticultural commodity produced in Lampung Province. The amount reached 1.208 million tons in 2020, down 0.05% from the previous year which was 1.209 million tons. The productivity of bananas in Lampung is 96.87 kg per clump in 2020. This study aims to, find an innovative recipe for substitute nastri products with wheat flour with kepok banana flour as an effort to diversify food, and determine public acceptance of banana flour nastar products. This research is grouped according to the 4D method, namely Define, Design, Develop, and Disseminate. In this study, wheat flour was substituted with banana kepok flour with concentrations of 20%, 30%, and 50%. The results showed that the acceptable substitution of banana kepok flour on nastar products was 20% and the preference test using the paired t test method showed that there was no difference in the level of preference for nastar flour substitution of wheat flour with banana kepok flour with ordinary nastar (control) so it can be interpreted that the product is can be accepted by the community Key words : Lampung, Banana Flour, Banana Flour Nastar